Identificación macroscópica de Stephanurus dentatus en cerdos faenados en el camal municipal del cantón Babahoyo - León Pivaque, Andrea Michel (2024)
Stephanurus dentatus is a nematode parasite that commonly affects pigs, especially in tropical and subtropical regions. Infection by this parasite can cause significant lesions in organs such as the kidneys, liver, and lungs, in addition to causing confiscations in slaughterhouses. The objective of this study was to macroscopically identify the presence of S. dentatus in pigs slaughtered in the municipal slaughterhouse of Babahoyo, Ecuador. A post-mortem examination of the kidneys was performed on 300 samples of slaughtered pigs. Variables such as age, sex, breed, and origin were recorded. Through direct observation and incision of the kidneys, signs of the parasite were sought, such as cysts or anatomical alterations. The results of the study showed a total absence of positive cases among all the samples analyzed. The incidence was 0% across all categories. This contrasts with previous research reporting variable prevalence rates of swine parasitosis according to region. The lack of detection of S. dentatus could be attributed to the effectiveness of preventive measures implemented with the animals prior to slaughter, as well as favorable environmental conditions that influence the low local prevalence of the parasite. The absence suggests a positive scenario in terms of the control of parasitic diseases in the area. It is concluded that there was no presence of the parasite in the examined organs of the slaughtered pigs. It is recommended to continue with the health controls and complementary studies to confirm the epidemiological situation in the region.